Napoleoński garnizon głogowskiej twierdzy w latach 1812-1814 = Napoleonic Garrison of the Fortress of Głogów in the years 1812-1814 - Helwig, Jarosław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
During the Napoleonic wars, the fortress of Głogów played an important role in the plans of both fighting parties. Its seizure in December 1806 enabled to unite safely the troops remaining under the command of Jerome Bonaparte (so-called allied army, consisting of Bavarian and Wurttembergian units ? later 9th Corps) with the main forces operating in Poland. After terminating military operations, the problems with paying off the contribution dictated to Prussia in Tilsit made Głogów, together with Szczecin and Kostrzyn, remain in the French hands, and the maintenance of the fortress of Głogów was assigned to the Prussians, which caused additional expenditures.
Keywords: Głogów - historia; wojsko napoleońskie; 19 w.